2015
DOI: 10.3944/aott.2015.14.0439
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable Are The Threaded Locking Screws?

Abstract: To avoid locking screw deformation, high threaded screws must not be used as locking screws. In cases of unreliable patients, 5-mm low threaded screws should not be used in the nailing of comminuted or oblique femur shaft fractures. All 5-mm unthreaded screws and 5.5-mm low threaded stainless steel screws can be used safely in full weight-bearing conditions of unreliable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The same experimental design was used by many researches with polyethylene tube [7][8][9], aluminium tube [13] -12] to obtain yield strength and yield point. With the polyethylene tube and aluminium tube to obtain true yield point was not likely as it was unreliable if the deformation that appears on the stress-strain graph belonged to polyethylene tube and its holes deformations or the locking screw deformation itself [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The same experimental design was used by many researches with polyethylene tube [7][8][9], aluminium tube [13] -12] to obtain yield strength and yield point. With the polyethylene tube and aluminium tube to obtain true yield point was not likely as it was unreliable if the deformation that appears on the stress-strain graph belonged to polyethylene tube and its holes deformations or the locking screw deformation itself [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that the stress on 1-mm deformation was defined as "yielding strength" instead of "true yield point [7-9, 14, 15]. It was concluded that due to the trapping of screws within the tube holes, the diameter of the metal tube hole must be 7 mm in order to clearly determine the true yield point [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations